188k views
5 votes
3x-5=x+1



Helpppppppppppp

User Patriks
by
5.4k points

2 Answers

6 votes
First you subtract 3x-x since they are like terms turning the equation into 2x-5=1. Then you add 5+1 because they are like terms making the equation 2x=6. Last you divide 6/2 to get x=3
User Joslyn
by
5.2k points
6 votes

Answer:

your answer is x= 3

Hope this helps!

User Dibstar
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.